Gut microbiota and liver disease. Issue 6 (June 2014) - Goel, Amit; Gupta, Mahesh; Aggarwal, Rakesh
Abstract Microbes are present in large numbers in each human being, in particularly in the gastrointestinal (GI) tract, and have long been believed to have some beneficial effects for their hosts. Till recently, however, we lacked tools for studying these organisms. Rapid technological advances in recent years have markedly improved our understanding of their role both in health and disease. Recent literature suggests that organisms in the GI tract, referred to collectively as gut microbiota, play an indispensable role in the maintenance of host's homeostasis. Alterations in the gut microbiota, that is in the nature and relative density of various constituent bacterial species, appear to have a role in pathogenesis and progression of several GI and hepatic diseases. This has also opened the vista for tinkering with gut flora in an attempt to treat or prevent such diseases. In this review, we have tried to summarize information on normal gut microbiota, laboratory techniques and animal models used to study it, and the role of its perturbations in some of the common hepatic disorders, such as non‐alcoholic fatty liver disease (including obesity), non‐alcoholic steatohepatitis, alcoholic liver disease, and liver cirrhosis and its complications.